Structured Analysis (SA): A Language for Communicating Ideas - Ross, D.T. (IEEE transactions on software engineering, 1977)
Structured analysis (SA) combines blueprint-like graphic language with the nouns and verbs of any other language to provide a hierarchic, top-down, gradual exposition of detail in the form of an SA model. The things and happenings of a subject are expressed in a data decomposition and an activity decomposition, both of which employ the same graphic building block, the SA box, to represent a part of a whole. SA arrows, representing input, output, control, and mechanism, express the relation of each part to the whole. The paper describes the rationalization behind some 40 features of the SA language, and shows how they enable rigorous communication which results frorn disciplined, recursive application of the SA maxim: "Everything worth saying about anything worth saying something about must be expressed in six or fewer pieces."